2022
DOI: 10.3390/polym14071416
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Consequences of Rubber Crumb Application: Soil and Water Pollution

Abstract: End-of-life tires are utilized for various purposes, including sports pitches and playground surfaces. However, several substances used at the manufacture of tires can be a source of concerns related to human health or environment’s adverse effects. In this context, it is necessary to map whether this approach has the desired effect in a broader relation. While the negative effects on human health were investigated thoroughly and legislation is currently being revisited, the impact on aquatic or soil organisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…The experimental results with the organisms of soil raise serious questions on earthworm mortality as well. [65] Recent studies on air monitoring by and Singh et al (2015a) reported that tire fires contribute to extensive emissions of sulphur dioxide, particulate matter 2.5, 19 distinct PAHs, and other hazardous, mutagenic, or carcinogenic pollutants. [66,67] Rainwater will readily pool in the hollow center of a tire, where it will serve as a breeding site for pests like mosquitoes.…”
Section: Worn Rubber Tires As Hazardsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results with the organisms of soil raise serious questions on earthworm mortality as well. [65] Recent studies on air monitoring by and Singh et al (2015a) reported that tire fires contribute to extensive emissions of sulphur dioxide, particulate matter 2.5, 19 distinct PAHs, and other hazardous, mutagenic, or carcinogenic pollutants. [66,67] Rainwater will readily pool in the hollow center of a tire, where it will serve as a breeding site for pests like mosquitoes.…”
Section: Worn Rubber Tires As Hazardsmentioning
confidence: 99%
“…The experimental results with the organisms of soil raise serious questions on earthworm mortality as well. [ 65 ] Recent studies on air monitoring by Downard et al. (2015) and Singh et al.…”
Section: Polymer Waste As An Issue Of Concernmentioning
confidence: 99%
“…One of these inventions was recycling tires into rubber crumb that can be used as the softfall surfaces for playground equipment. However, an unintentional downside to this recycling solution has found the rubber crumb softfall to be a source of microplastic pollution [ 35 ]. AUSMAP, a globally recognized citizen science program in Australia, worked in collaboration with ReefClean to investigate rubber crumb loss from playgrounds in the Great Barrier Reef catchment [ 36 ].…”
Section: Sources Of Microplastic Pollutionmentioning
confidence: 99%
“…Artificial turf fields, also called "synthetic" surfaces, are widely used as an alternative to natural grass in many areas such as residential areas, parks, playgrounds and playing fields. (1) Although the reason given as to why artificial turf grounds are widely used in sports and playgrounds is that they allow useful activities such as exercise, it is reported that the main reason is cost savings and the ability to use artificial grass fields in all weather conditions. Crumb rubber from tires contains various metals such as cadmium, chromium, zinc, aluminum and lead.…”
Section: Introductionmentioning
confidence: 99%